2016
DOI: 10.1007/s10739-016-9449-4
|View full text |Cite
|
Sign up to set email alerts
|

“The Theory was Beautiful Indeed”: Rise, Fall and Circulation of Maximizing Methods in Population Genetics (1930–1980)

Abstract: Describing the theoretical population geneticists of the 1960s, Joseph Felsenstein reminisced: "our central obsession was finding out what function evolution would try to maximize. Population geneticists used to think, following Sewall Wright, that mean relative fitness, W, would be maximized by natural selection" (Felsenstein 2000). The present paper describes the genesis, diffusion and fall of this "obsession", by giving a biography of the mean fitness function in population genetics. This modeling method de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In this sense, FD selection is one of several forms of adaptive evolution that can, in principle, reduce population fitness (Grodwohl, 2017;Leigh, 1977;Moran, 1963;Rankin, Bargum, & Kokko, 2007).…”
Section: We Ask the Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, FD selection is one of several forms of adaptive evolution that can, in principle, reduce population fitness (Grodwohl, 2017;Leigh, 1977;Moran, 1963;Rankin, Bargum, & Kokko, 2007).…”
Section: We Ask the Questionmentioning
confidence: 99%
“…Rather, FD selection can, in some cases, drive evolutionary reductions in population fitness (Wright, 1942). This insight of Wright's is sometimes overlooked, given his tendency to emphasize fitness maximization in other contexts of natural selection (reviewed in Li, 1955;Grodwohl, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, apart from even adding mutations, Patrick Moran and Richard Lewontin demonstrated that fitness is not guaranteed to maximize if epistasis and gene linkage are modeled. Grodwohl characterized these shocking mathematical developments as "The Rise and Fall of Fitness Maximization" (Grodwohl, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps it is too optimistic to assume that an overlap of the chosen trait would have been sufficient to spark crossfertilization of these fields: quantitative genetics, with its interest in predicting ongoing microevolution, and optimization approaches to life-history theory, which has the goal of trying to predict the precise location of the ultimate fitness peak, are to this day not cross-referencing each other very frequently. Attempts to point out equivalences and relationships between them exist [25][26][27][28][29][30][31][32][33] but for some reason do not appear to build much information flow between the mainstream currents of each field. As is, the insights in [20] have had a major impact on life-history theory, less so on the continued discussion that has Fisher [5] and Cooke et al [15] at its origin.…”
Section: The Life-history Anglementioning
confidence: 99%